UTD-Based Analysis of Antenna Radiation Patterns on PEC Surfaces with Thin Material Coating - Kittisak Phaebua; Titipong Lertwiriyaprapa; Chuwong Phongcharoenpanich; Prabhakar H. Pathak (My University, 2025)
This study explores the application of the Uniform Geometrical Theory of Diffraction (UTD) to examine how material coatings influence the radiation pattern of a slot array antenna placed on a curved surface. The analysis considers a range of dielectric constants for the coating materials. The UTD framework for coated cylindrical geometries is employed to simulate the electromagnetic (EM) wave behavior of the antenna. A uniformly aligned slotted array antenna is evaluated using the UTD-based radiation model. Numerical results are provided to demonstrate the effects of the coating material on radiation pattern characteristics, including side-lobes and back-lobes. The findings are validated through comparison with results from commercial EM simulation software, showing strong agreement.
Keywords: Electromagnetic Scattering and Analysis; Advanced Antenna and Metasurface Technologies; Antenna Design and Analysis